A Dynamic Study between Export from China to South Korea and Economic Growth in China - Yugang He; Eunmo Lee (Universitas Negeri Malang, 2018)
This paper applies annual data from 1998 to 2016 to search for the dynamic operating mechanism between export from China to South Korea and economic growth in China. The vector error correction model is utilized to conduct an empirical analysis. The results indicate that there is a long-run relationship between them. In more specifically, if the export from China to South Korea increases by 1 per cent, the economic growth in China will increases by 0.769 per cent. Meanwhile, the result of Granger causality test also reveals that there is an unidirectional causality between them exists under 5 per cent significance level. More importantly, the result of vector error correction mechanism shows that when the economic growth is derivate from the long-run equilibrium in the short run, it will return to the long-run equilibrium by 2.2 per cent. Keywords: Economic Growth, Export from China to South Korea, Vector Error Correction ModelJEL Classification: C02; F10; F19